Evaluating the therapeutic efficacy of ozone liquid dressing in healing wounds associated with bullous pemphigoid - Li Li; A’chong Feng; Jianyun Lu; Hongye Liu; Wenli Xue; Hongzhou Cui (Scientific Reports)
Abstract Bullous pemphigoid (BP) is a chronic autoimmune condition characterized by painful blistering wounds. While effective, conventional treatments often have significant side effects. This study evaluates the therapeutic efficacy of Ozone Liquid Dressing (OLD), an innovative adjunct treatment, in enhancing wound healing, reducing infection rates, and alleviating pain associated with BP. A total of 120 BP patients were assigned to either an observation group (standard care + OLD) or a control group (standard care alone). The dressing was applied daily until wound healing, or the two-week observation period concluded. Efficacy was measured by healing rates, infection reduction (assessed by positive bacterial cultures in wound exudates), and pain levels (assessed by the Numeric Rating Scale, NRS). Statistical analyses were performed using SPSS software, employing t-tests and Chi-square tests as appropriate. The observation group showed significantly higher complete healing rates (61.70% vs. 38.33%, p < 0.05) compared to the control group. In terms of overall efficacy, the observation group achieved 91.70%, compared to the control group’s 80.00% (p = 0.116). A marked reduction in positive bacterial cultures was observed in the observation group, beginning on day 3 (p < 0.01), and pain scores decreased significantly by day 10 (p < 0.001). OLD significantly enhances wound healing and reduces pain in BP patients, demonstrating clinical potential. Further studies are necessary to confirm the long-term benefits and clinical applicability of OLD in managing BP wounds.